From Preparation to Presentation: Student Nurses' Transformative Research Dissemination Journeys at Off-Campus Academic Conferences - Bimuyag, Jayson; Gaerlan, Christopher Ian (Journal of Interdisciplinary Perspectives, 2024)
Academic conferences play a crucial role in enhancing undergraduate research productivity, yet more research is needed on student nurses' experiences during the dissemination phase of their research. This study employed qualitative content analysis to examine 33 learning journals from 25 student nurses, focusing on their experiences from the preparation stage to the presentation of their group research at off-campus academic conferences. The analysis revealed two main themes: Transformative Pathways to Research Presentation and Transformative Power of Research Presentation. The first theme encompasses categories such as Psychological Preparedness Challenges, Logistical Challenges, Supportive and Collaborative Networks, and Mastery through Practice. The second theme includes categories like Unleashing Confidence, Learning through Observation and Adaptation, Interactive Presentation Experiences, and Nurturing Growth through Research. The findings highlight the challenges faced by student nurses and the transformative experiences they encountered from preparation to presentation at off-campus academic conferences. Despite these challenges, student nurses showed significant personal and professional growth, overcoming psychological preparedness issues and logistical hurdles while seeking mastery through practice. The transformative power of research presentations was evident as they gained confidence and refined their presentation skills.